Plasma level of calcitonin gene-related peptide in the diagnosis of episodic migraine with comorbid conditions - O. Ye. Dubenko; A. O. Chernenko (Zaporožskij Medicinskij Žurnal)
Comorbid and co-occurring diseases are risk factors for the progression of episodic migraine to chronic migraine. Biomarkers for migraine could help with diagnosis and treatment selection and monitoring.